University Training of STEM-IT Professionals to Innovation Activity in 3D-Teams - A. I. Chuchalin (Высшее образование в России)
The paper focuses on the training professionals in the field of natural sciences, engineering and technology, mathematics and IT with different levels of education and qualifications (bachelor, master, doctor) for joint innovation activity in interdisciplinary 3D teams. The paper substantiates the need for such training, which stems from digitalization and introduction of Industry 4.0 tools, as well as the desire to overcome the technological backlog of the country. Based on the analysis of the best world practices of innovation activity, the paper proposes to coordinate programs for training of STEM-IT professionals for effective collaboration in 3D-teams by planning the competencies of graduates, taking into account the priorities of scientists, engineers, technologists, mathematicians and IT specialists when working with the division of labor in a team at various stages of creating science-intensive innovative products, systems, processes, and services. The purpose of the research is to develop recommendations for program coordination.